Pengaruh pelatihan berbasis media elektronik pintar kemenag dan webinar musyawarah guru mata pelajaran dan kinerja guru PAI di mts kabupaten Indragiri Hilir - Hasnawati, Hasnawati; Murhayati, Sri; Idris, Idris (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2025)
This study aims to examine the impact of the Ministry of Religious Affairs’ Smart Electronic Media Training and the Subject Teachers’ Forum (MGMP) webinars on the performance of Islamic Education (PAI) teachers at Madrasah Tsanawiyah in Indragiri Hilir Regency. A quantitative approach was employed, using a correlational method. Data were collected through questionnaires, observations, and documentation, and analyzed using simple and multiple linear regression techniques. The results show that: (1) the Smart Electronic Media Training has a significant effect on teacher performance, with an F-value of 689.661 and a significance level of 0.000 < 0.05, and a coefficient of determination (R²) of 0.981, indicating a 98% contribution; (2) the MGMP webinars also significantly affect teacher performance, with an F-value of 293.136, a significance level of 0.000 < 0.05, and an R² of 0.958, or 95%; (3) simultaneously, both variables have a significant combined effect on teacher performance, with an F-value of 338.051, a significance level of 0.000 < 0.05, and an R² of 0.983, or 98%.These findings demonstrate a strong positive contribution of both the training and the webinars to improving the performance of Islamic Education teachers.